A study of the Fischer-Tropsch synthesis at elevated temperatures in a shock tube. - Kelly, Raymond James. (2013)
The shock tube was used to investigate the product spectrum of the initial stages of the Fischer-Tropsch synthesis carried out at elevated temperatures. Special attention was paid to the relationship between methane selectivity and temperature. The range of reaction environments studied are summarised below:- Reaction temperature 780 K - 1425 K. Reaction pressure 160 psia - 330 psia. Mean reaction time 628 u sec. - 727 u sec. Test gas composition - argon 81 - 87 mol. %. - hydrogen 6,5 - 9 mol. %. - carbon monoxide 6,5 - 9,5 mol.%. Catalyst type - fused iron, triply promoted. Catalyst loading - 0,12 - 0,14 mass catalyst / mass gas. The experiments were conducted in the incident shock region and quenching was achieved by the reflected rarefaction wave. Percentage conversion of hydrogen and carbon monoxide to useful products (hydrocarbons) varied between 0,1 and 2. Products detected in measurable quantities were methane, ethylene, ethane and propylene. The theory of shock tube wave propagations through heterogeneous medi a was studied in detail and unique theory developed for handling conditions of varying temperature and pressure. This enabled characterisation of the reaction environment so that multilinear regression could be used to find a correlation between H2 + CO consumption and system variables. Major information gleaned on the initial stages of the Fischer-Tropsch synthesis at elevated temperatures was; (i) contrary to observed trends under normal synthesis conditions, methane selectivity decreased and propylene selectivity increased with increasing temperature; (ii) the process appeared to be hydrogen adsorption, pate controlled; (iii ) molecular degradation processes played a negligible part in the format ion of final reaction products, and (iv) oxygen compounds, such as methanol, did not appear to be important intermediate products. It has been shown that the heterogeneous shock tube offers a possible means of obtaining initial reaction rate data for highly complex systems. === Thesis (Ph.D.)-University of Natal, 1973.